Features of optical properties of ferromagnetic semiconductors with dynamic laser-induced gratings - Semchuk, O.Yu.; Veskliarskii, R.Z.; Kosharskii, K.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Nonlinear optical phenomena in ferromagnetic semiconductor with dynamic grating created by coherent light beams are investigated. A high-frequency current and nonlinear absorption coefficient are calculated. It is shown that with increasing wave frequency, the nonlinear absorption coefficient grows and reaches the maximum at frequency ω ≈ 3•10¹² s⁻¹, and then smoothly decreases at higher frequencies. Therefore, the second term of the nonlinear absorption coefficient is modulated with coordinate. This proves that a dynamic grating emerges in ferromagnetic semiconductor.